The effect of irrigation with wastewater fish ponds on the quality of peanut, (Arahis hypogeae) - Othman, Ali S.; Abd Al-Aziz, M.; Haifa, S.; Saad, Adib Ali (Iraqi Journal of Aquaculture, 2019)
The research was carried out at Alsen research center of the General Authority for Fisheries in the Banias region–Tartus Governorate - during two agricultural seasons 2018-2019, in order to study the effect of irrigation with fish culture effluent on some morphological characteristics and some productive characteristics of peanut yield (Syrian 1). The experiment consisted of five treatments: Irrigation with freshwater. (control, T1), irrigation with fish culture effluent (T2), irrigation alternately with fish culture effluent tri and freshwater once (T3), irrigation alternately with fish culture effluent once and freshwater once (T4), irrigation alternately with fish culture effluent once and freshwater tri (T5). The experiment was done according to the completely randomized block design with three replicates. Soil and water samples were collected and analyzed. Results of the study showed: The irrigation in waste water fish ponds adds positive effect on the morphological characteristics and improves the productive characteristics. It was observed that irrigation with water of mature fish ponds exceeded of the witness.(control). The research concluded to highlight the importance of using the drainage water of fish ponds to irrigate the peanut crop (Syrian-1) for the richness of this water with dissolved solids.